GENETIC DISTANCE AND ITS RELATION TO THE PERFORMANCE OF INTRAHIRSUTUM Fl HYBRIDS - Baloch, Mohammad Jurial (Biological Sciences - PJSIR, 2003)
Present stud,· ll’as i n i tiated to determi ne as ho fa r genetic di sta nce i s irnpo11ant in the expression of hetero si s i n some cotton lea f cu rl virus resista nt and other i ntrah i rsutu m F, h ybrid s. Three sets of h> ·brids , ere developed: J ) highl\’ adapted Cotton Research Institute Sakrand (CRIS) lines crossed "ith exotic li nes. 2) CIUS lines crossed ith Cotton Research Insti tute Mul tan (CIM) li nes, 3) the CRIS lines crossed with CRIS li nes. For seed cotton vield. n um ber of bolls formed and fi bre length, the hybrids developed Crom exotic li nes expressed more percent of heterosi s than hYbrids obtained from t he crosses of CRIS vv"ith CIM or CRIS wit h CRIS lines that suggested that genetic distance is ver, i m po11ant i n the expression or heterosis for these traits. The average better parent hetero sis of Exotic. CIM, and CRIS lwbrids respecti vely were; !(JG. 42.2 and 22.8 for seed cotton yield. 77. J , 44.3 and 25.2% for n um ber of bolls and 5.8. 4.8 and 4.6% for fi ber length. In respect to lint%. all the th ree sets of h1·brid s expressed negative mean heterosi s whereas for seed i ndex, CR1S x CIM hvbrids expressed mea n heterosis of 1 3.5% against 4.7% of’ CRIS x Exotics a nd 3.3% or CRlS x CRIS hybrid s. Consideri ng the performance of i nd j, ·id ual h,·brid s, CRJS-l 21 x CP-15 -12 wh ich gaYe maxi m um yield of 1 46.5 also prod uced highest boll s of 52. l , whereas hvbrid CRJS- J 68 x CIM-443 gin ned m axim um o[38.8% lint also gave highest seed i ndex oC 7.8 gm and for fi bre length , CRlS-12 1 x CIM-443 pmd uced longer tibre of’ 2<J.2 111111.